Computational fluid dynamics simulation of the resistance of ships in calm water - Leong, Jackson Wei Jian (Nanyang Technological University, 2021)
Computational Fluid Dynamics (CFD) for hydrodynamic design of ships have been progressing significantly within the last decade towards providing a quick, cost efficient and stable platform which can model an extensive range of problems that closely mimics the actual behavior of the vessel, such as ship’s resistance, propulsion, seakeeping, maneuvering, etc. Among all these characteristics, calm water resistance simulation is considered the most vital but basic application, thus the project will focus on estimating the resistance on the Duisburg Test Case (DTC) using an Open-source CFD software OpenFoam, to review and investigate the software’s potential as an alternative method to estimate the resistance and wave making characteristic compared to traditional empirical and experimental approach. In addition, to investigate the side wall effect of the towing tank by modelling an open sea and towing tank simulation condition and performed basic visualisation analysis using Paraview. For the numerical simulation interFoam will be used for predicting the resistance and free surface capturing, the solver is derived from the Reynolds average Navier-Stokes (RANS) with free surface modelling capability using Volume of Fluid (VoF) method. The results will be compared with the experimental towing tank results test provided by a Norwegian Marine Technology Research Institute (MARINTEK), the paper will also include the visualization study of the free surface wave component, wake fields and pressure distributions. Through our work, the huge potential of CFD application in calm water simulation prediction is demonstrated, the project has also contributed to the development and understanding of ship hydrodynamics resistance and wave making characteristic through OpenFOAM, providing an accurate analysis apart from using other conventional methods, giving modern ship designers a more robust estimation methodology in predicting the ship’s hydrodynamic characteristic such as the resistance in calm water.